Injection-moulding compounding of PP polymer nanocomposites - Battisti, Markus Gottfried (Strojniški vestnik, 2013)
The objective of this study is the comparison of different compounding techniques and their influence on the Youngs modulus. Both, conventional processing of polymer nanocomposites and processing in the worldwide unique Injection Molding Compounder (PNC-IMC) were evaluated. Additionally the effects of nanofillers on the thermal conductivity of polymer nanocomposites were investigated at various pressures.In comparison to the conventional compounding process, where the compound has to be pelletized and fed into the injection molding machine for the second plasticizing process, the injection molding compounding combines these two processing steps. The material compounding and the subsequent injection molding are done directly by only one plasticizing process by the use of a heated melt line and a melt accumulator. In this study, both of these techniques were used for the production of polymer nanocomposites. This paper shows the different effects of processing techniques, screw speed, counter-pressure and different extruder length on the Youngs modulus and demonstrates that for the improvements a compromise between shear energy input and residence time is essential. The increase of thermal conductivity by using nanofillers compared to the virgin polypropylene is shown. The investigated increase in thermal conductivity should be very interesting for the industry in terms of cycle time reduction in the injection molding process. These very first results give a good overview on both the possibilities and the limitations of the innovative concept of the PNC-IMC. Further studies on the detailed understanding concerning exfoliation and intercalation of layered silicates in polymer melt will be done.
Keywords: brizgalni kompaunderji; eksfoliacija; exfoliation; injection moulding compounding; intercalation; interkalacija; layered silicates; polimerni nanokompoziti; polymer nanocomposites; silikati v plasteh; thermal conductivity; toplotna prevodnost